Challenges of Diagnosing Viral Anterior Uveitis. (3rd September 2017) - Groen-Hakan, Fahriye; Babu, Kalpana; Tugal-Tutkun, Ilknur; Pathanapithoon, Kessara; de Boer, Joke H.; Smith, Justine R.; de Groot-Mijnes, Jolanda D.F.; Rothova, Aniki
ABSTRACT: The viral causes of anterior uveitis (AU) emerged with the use of novel molecular diagnostic tests and serologic tests adapted for small volumes (Goldmann-Witmer Coefficient). The viral causes of AU may be underestimated, and some of the presumed idiopathic AU cases will probably be proven to be of viral origin in the coming years. So far, a viral origin of AU was suspected in patients who presented with unilateral hypertensive AU. It is not clear which clinical presentations should raise a suspicion of viral etiology. There is an overlap in the clinical manifestations of AU caused by viruses and other non-viral forms of AU. A viral cause of AU should be suspected in patients with unilateral AU, exhibiting small or medium sized KPs, some form of iris atrophy, high IOP and early development of a cataract and the definitive diagnosis can be proven by aqueous humor analysis.